Use of the integrated profile for voluntary muscle activity detection using EMG signals with spurious background spikes: A study with incomplete spinal cord injury. (February 2016) - Liu, Jie; Liu, Qiuping
Abstract: Following neurological injuries, such as spinal cord injury (SCI), voluntary muscle activity detection from electromyography (EMG) signals can be problematic due to spurious involuntary spikes produced by physiological and extrinsic/accidental origins. The purpose of this study was to demonstrate the usefulness of the integrated profile for voluntary muscle activity detection in the presence of spurious background spikes for SCI patients. Two onset detection methods (the sample entropy analysis and the integrated profile) were evaluated using both semi-synthetic and experimental surface EMG signals with spurious background spikes recorded from SCI patients. For all the examined signal to noise ratios, the integrated profile method was able to achieve comparable performance with the sample entropy analysis-based method but while taking significantly shorter running time ( P < 0.001). The findings suggest the integrated profile method is robust with large involuntary spikes in the baseline signal and can highlight voluntary muscle contractions.